Identification of Heavy Metals from Ten Watering Campuses (Ground Waters) of Ilam-Iran - Naghipoor, Ali; Abbasi, Shahryar; Hajighasemi, Zahra; Beiranvandi, Darab; Farmani, Abbas (Asian Journal of Chemistry, 2010)
Thirteen elements As, Ba, Cd, Co, Cr, Cu, Hg, Fe, Ni, Pb, Se, Sn and Zn in 10 watering campuses of ground waters in Ilam state, Iran were detected by inductively coupled plasma (ICP) in aqueous samples. The results show that all the 13 elements have concentration in the range of standard based on WHO, Iran, USA and European standards of drinking water.